2018
DOI: 10.3390/ma11101999
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Bi-Axial Mechanical Properties of Warp-knitted Meshes with and without Initial Notches

Abstract: Warp-knitted meshes have been widely used for structural reinforcement of rigid, semi-rigid, and flexible composite materials. In order to meet the performance requirements of different engineering applications, four typical warp-knitted meshes (rectangular, square, circular, and diamond) were designed and developed. The mechanical behaviors of these meshes under mono-axial and multi-axial tensile loads were compared. The influence of the initial notch length and orientation on the mechanical performance was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Uniaxial tensile test is used widely, usually the sample size and loading rate are slightly different. 25,26 Yang et al studied the mechanical properties of the protective nets with different polyethylene monofilament diameters and knitting densities, including tensile stress along with the fabric in three directions with 0°, 45°and 90°. 27 The results indicated that several kinds of protective mesh show good mechanical properties.…”
Section: Performances Of Mesh-fabricsmentioning
confidence: 99%
“…Uniaxial tensile test is used widely, usually the sample size and loading rate are slightly different. 25,26 Yang et al studied the mechanical properties of the protective nets with different polyethylene monofilament diameters and knitting densities, including tensile stress along with the fabric in three directions with 0°, 45°and 90°. 27 The results indicated that several kinds of protective mesh show good mechanical properties.…”
Section: Performances Of Mesh-fabricsmentioning
confidence: 99%
“…The current research on the biaxial or multiaxial mechanical properties of materials generally focuses on composite materials with woven fabrics as reinforcements and films. Shao et al 14 and Bigaud et al 15 proposed the biaxial constitutive relationship of composite materials with woven fabric as the reinforcing material and a new failure criterion. Chen et al 16,17 focused on the tear analysis of typical airship hull materials.…”
mentioning
confidence: 99%
“…The research on the mechanical properties of warpknitted fabrics mostly focuses on tensile mechanical properties, tearing properties and the influence of notches on mechanical properties. 7,14,[18][19][20] Research on biaxial stretching is rarer, with no mention of metal mesh. At present, most researches on metal meshes concentrate on the electrical performance of large retractable satellite antennas, such as the work of Li et al 12 and Shao et al, 21 who researched the application of metal mesh to satellite antennas, studied the influence of its coating, structure and other factors on its electrical performance, and used derived analysis methods such as the equivalent regular grid unit of the strip model.…”
mentioning
confidence: 99%
See 2 more Smart Citations